THE READABILITY ON GET ALONG WITH ENGLISH TEXTBOOK FOR VOATIONAL SCHOOL OF ELEVENTH GRADE STUDENTS AT YAPIM SIMPANG KAWAT - Djuwi Adiba; Anni Holila Pulungan, (Universitas Negeri Medan, 2017)
The objective of this study aimed to find out the textbook that is readable for vocational school of eleventh grade students at YAPIM. It also used descriptive method to analyze and describe the readability based on SMOG and the New Dale-Chall formula. The data are the sentences in the six texts taken from the textbook published by Erlangga. The findings shows that the readability score based on SMOG formula looks like: text 1 got 134.43 in grade 15, text 2 got 89.98 in grade 12, text 3 got 25.88 in grade 8, text 4 got 85.89 in grade 12, text 5 got 15.75 in grade 7, and text 6 got 53.31 in grade 10. The average of the score was 67.54. Meanwhile, the readability score based on the New Dale-Chall formula looks like: text 1 got 8.0525 in grade 11-12, text 2 got 7.6315 in grade 9-10, text 3 got 5.0865 in grade 5-6, text 4 got 8.9655 in grade 11-12, text 5 got 5.5505 in grade 5-6, text 6 got 6.7285 in grade 7-8. The average of the score was 7. It shows that based on the average of the score from those formulas, the textbook is readable for the eleventh grade students.